Sensitivity of freshwater algal communities to environmental variables in Betty's Bay and Onrust in the Western Cape, South Africa - Lannas, Kathryn S.M (Department of Biological Sciences, 2019)
This study was a first attempt at investigating whether algal groups respond to environmental differences including human impacts in wetlands in the Western Cape of South Africa. Samples were collected from three permanent and three temporary wetlands in Betty's Bay and a temporary wetland in Onrust, near the town of Hermanus. The environmental variables which were measured were pH, conductivity, water depth, whether wetlands were temporary or permanent and whether the samples were from the wetland or from waterlogged soils next to the wetlands. The wetlands sampled were found to be very similar and overall there was not a strong species response to the environmental variables. When only the diatom species data were analysed, however, it was possible to differentiate between samples from Bass Lake and Vermont Vlei. These wetlands had contrasting pH and conductivity values, with Bass Lake having an average pH of 6.8 and a mean conductivity of 262.5 µSiem and Vermont Vlei having an average pH of 8.4 and 152.1 µSiem for the average conductivity value. This suggests that diatom species are sensitive to small differences in pH and conductivity. Diatoms were found on average to make up 91 % of the taxa sampled in the different wetlands and were ubiquitous in their distribution among the different wetlands. The algal taxa that occurred in the greatest number of samples included Amphora sp., Cymbella sp., Navicula sp., Nitzschia sp., Pinnularia sudetica, Rhizoclonium hieroglyphicum, Surirella sp. and Synedra sp .. The average Shannon-Wiener biodiversity index was 3.53 for the seven wetlands. It is recommended that in future studies there should be greater standardisation in sampling with specific micro-habitats sampled to make algal groups comparable. It is also possible that a greater number of wetlands with a wider range in water chemistry properties are needed to be able to detect clear algal species responses to environmental gradients.